Tourism's lost leaders: Analysing gender and performance. (March 2017) - Pritchard, Annette; Morgan, Nigel
Highlights: Scrutinizes performance indicators, which make and mark tourism leaders. Analyses editorial boards, professorships and publication metrics. Reveals gender inequality in tourism's organisational practices. Questions the efficacy of tourism's pipeline to equity. Identifies routes to gender equity and presents a manifesto for diversity action. Abstract: Higher education is increasingly engaged with diversity initiatives, especially those focused on women in academic leadership, whilst there is an evolving literature across the humanities and the social, management and natural sciences, critiquing academia's gendered hierarchies. In contrast, senior academics in the field of tourism management have largely eluded similar sustained analysis. This paper builds on recent gender-aware studies of tourism's leading academics with three aims. Firstly, to widen evidence of gendering in tourism's academic leadership by scrutinizing and contextualizing performance indicators, which make and mark its leaders and shape its knowledge canon. Secondly, since critique alone cannot lead to transformation, the paper seeks to 'undo' gender in tourism's academy. Thirdly the paper presents interventions to accelerate academic gender equity.